06 Dual Energy CT has the Potential to Improve Non-Invasive Identification Of Necrotic Core. (20th November 2012) - Obaid, D; Calvert, P; Goddard, M; Gopalan, D; Rudd, J; Bennett, M
Abstract : Background: CT can classify plaque based on its x-ray attenuation. However, identifying vulnerable plaque is limited by overlap between the attenuation of necrotic core and fibrous plaque. Changes in attenuation of plaque components to x-rays of differing energies may allow better discrimination. We tested whether Dual Energy CT (DECT) (simultaneous image acquisition at two energies) improved identification of necrotic core, both in-vivo and ex-vivo. Methods: 20 patients underwent DECT and 3-vessel Virtual Histology-IVUS (VH-IVUS). Attenuation was sampled in 1088 plaque areas co-registered with VH-IVUS and used to define dual energy indices (changes in attenuation of plaque components at 100 kV and 140kV). 42 plaques were analysed by DECT to determine whether DECT increased sensitivity to detect VH-IVUS defined necrotic core. 10 post-mortem coronary arteries were also examined with DECT prior to histological analysis to determine whether DECT increased sensitivity to detect histologically proven necrotic core. Results: Dual energy indices of necrotic core and fibrous plaque were significantly different (mean: 0.0071 vs. 0.0283, p<0.05). Utilising these increased diagnostic accuracy for DECT to detect necrotic core in 87 segments of post-mortem arteries (sensitivity-64%, specificity-96%) compared with single energy CT (sensitivity-54%, specificity-92%). Sensitivity to detect necrotic core was lower in plaques analysed in-vivo due to the impact of temporal resolution on moving coronaries. However, DECT still provided marginal improvements in sensitivity (45%) compared with single energy CT (39%). Conclusions: Dual Energy CT has the potential to improve the differentiation of necrotic core and fibrous plaque allowing more accurate non-invasive identification of vulnerable plaque.